2016
DOI: 10.1007/s12020-016-1081-8
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, pattern, and outcome of recurrences after gamma knife radiosurgery for pituitary adenomas

Abstract: Gamma Knife radiosurgery is often used in pituitary adenomas. Aim of our study is to describe the characteristics and long-term outcome of patients with adenoma recurrence after Gamma Knife radiosurgery. We conducted a retrospective analysis of patients with pituitary adenoma treated by Gamma Knife radiosurgery between 1994 and 2014. Tumor recurrence was labeled as "in field" when the tumor growth occurred adjacent or within the prescribed isodose, whereas it was classified as "out of field" when the tumor gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 24 publications
0
14
1
1
Order By: Relevance
“…The tumor regrowth in field was more frequent than out of field (66.7 VS 33.3%) in our study. In the study of Losa et al (18), of the 26 patients, there were 18 patients (69.2%) developed recurrence out of field, which was higher than our study. We found previous surgery was significantly associated with tumor regrowth out of field (p = 0.033).…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…The tumor regrowth in field was more frequent than out of field (66.7 VS 33.3%) in our study. In the study of Losa et al (18), of the 26 patients, there were 18 patients (69.2%) developed recurrence out of field, which was higher than our study. We found previous surgery was significantly associated with tumor regrowth out of field (p = 0.033).…”
Section: Discussioncontrasting
confidence: 73%
“…The actuarial tumor control rates were 100%, 90%, 90%, 68%, and 68% at 1, 3, 5, 10 and 15 years after repeat GKRS, respectively. In previous studies, 0-9.6% of NFPA patients occurred tumor recurrence after GKRS (11,(13)(14)(15)(16)(17)(18). In a large study of 543 patients with pituitary adenomas by Losa et al (18), there were more patients with NFPA than functioning pituitary adenomas had a tumor recurrence (9.6% VS 4.8%).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Another study by Sheehan and colleagues indicated that GKRS treatment of patients with CD after failed TSS could result in 63% of the patients achieving normal 24-h urinary free cortisol (UFC) levels; however, 16% of the patients obtained new endocrine deficiencies (27). Losa et al (28) conducted another retrospective analysis of patients with pituitary adenoma treated by GKRS and found that patients with NFPAs have more frequent recurrence of disease than patients with hormone-secreting adenomas (9.6 vs. 4.8%). The 10-year progression-free survival in patients with NFPAs was 78.7%, which is much lower than that in patients in hormone-secreting adenomas (93.3%).…”
Section: Management Of Refractory Pasmentioning
confidence: 99%